2012
DOI: 10.1111/1471-0528.12059
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation in pregnant women with mental disorders: a cohort and nested qualitative study

Abstract: ObjectiveTo investigate whether 1) pregnant smokers with mental disorders are less likely to accept referrals to smoking cessation services compared with pregnant smokers without disorders; 2) they experience specific barriers to smoking cessation.DesignCohort study supplemented by cross-sectional survey and nested qualitative study.SettingThree maternity services, London, UK.PopulationPregnant smokers with and without mental disorders.MethodsCase notes were examined on a cohort of 400 consecutive pregnant smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 48 publications
2
42
0
16
Order By: Relevance
“…[110][111][112][113][114][115][116][117][118][119][120] This is a consistent finding in the literature that has been described since members of our team first conducted research with disadvantaged women in the 1970s. 151 The importance of smoking to reduce stress was also described by partners and HPs.…”
Section: Stress and Enjoymentsupporting
confidence: 77%
“…[110][111][112][113][114][115][116][117][118][119][120] This is a consistent finding in the literature that has been described since members of our team first conducted research with disadvantaged women in the 1970s. 151 The importance of smoking to reduce stress was also described by partners and HPs.…”
Section: Stress and Enjoymentsupporting
confidence: 77%
“…(17) Therefore, actions to assist pregnant women with mental disorders to quit smoking since the beginning of pregnancy should be considered for the promotion of mother and fetus health, as well as the interaction of health care teams of women and those dedicated to tobacco control, since the strategies usually applied to the general population in the cessation of smoking should be modified for pregnant women with mental disorders. (8) Successful and strongly indicated experiences are brief interventions, led by cognitive therapy framework. (6) A survey raised the difficulties of a pregnant woman with mental disorder, construction and training for specific coping.…”
Section: Discussionmentioning
confidence: 99%
“…(6) A survey raised the difficulties of a pregnant woman with mental disorder, construction and training for specific coping. (8) A previous study of pregnant women was conducted in the USA and revealed that alcohol provides an increase in both use of tobacco and in its dependency on the gestational period. (18) During pregnancy, the prevalence of the alcohol was lower (15%) than that of tobacco (46%) increasing with the multiuse (44%) of drugs such as alcohol, tobacco and cannabis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations